2004
DOI: 10.1093/rpd/nch286
|View full text |Cite
|
Sign up to set email alerts
|

Active personal dosemeters for individual monitoring and other new developments

Abstract: In this paper, we will present a first (but not complete) status description of active personal dosemeters (APDs) and their implementation in European countries. In modern radiation protection practices, APDs are becoming absolutely necessary operational tools for satisfying the ALARA principle. Despite their success, they are relatively new for individual monitoring of workers. Regulation, legal requirements and calibration procedures are different in European member states. A catalogue of commercially availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…These electronic personal dosimeters were attached outside the lead apron on the breast pocket. The semi conductor-based dosimeter provides a direct read of the occupa tional dose equivalent, H p (10), at a resolution of 1 µSv and is sufficiently sensitive for measurement of relatively low photon energies [5]. The elec tronic personal dosimeter was used in addition to the required thermoluminescent personal dosimeter [6].…”
Section: Assessment Of Occupational Effective Dosementioning
confidence: 99%
“…These electronic personal dosimeters were attached outside the lead apron on the breast pocket. The semi conductor-based dosimeter provides a direct read of the occupa tional dose equivalent, H p (10), at a resolution of 1 µSv and is sufficiently sensitive for measurement of relatively low photon energies [5]. The elec tronic personal dosimeter was used in addition to the required thermoluminescent personal dosimeter [6].…”
Section: Assessment Of Occupational Effective Dosementioning
confidence: 99%
“…In addition, by redesigning the geometric con guration of the support units, the eld could be used for other types of gamma-ray dosimeters. 4,7,8) An irradiation eld for neutron dosimeters will be reported elsewhere.…”
Section: Cs and 60mentioning
confidence: 99%
“…Many designs of active neutron dosimeters have been proposed and some are available commercially. A thorough review of active personal dosimeters was performed by Bolognese-Milsztajn et al [6] who found that most commercially available units suffer from a severe energy dependence that can lead to the underestimation the dose equivalent of up to a factor of 100 at some energies [6]. These devices usually have, as the sensing element, a Silicon pin diode surrounded by 10 Bi or 6 Li rich secondary charged particle "producer".…”
Section: Full Articlementioning
confidence: 99%